KEMITRAAN ANTARA LAPAS DENGAN PESANTREN DALAM RANGKA MENCARI SOLUSI TERHADAP OVER KAPASITAS PENGHUNI LAPAS - Henry Arianto (Jurnal De Lege Ferenda Trisakti, 2023)
The overcapacity of prisons in Indonesia is an open secret. This has a negative impact and sometimes even leads to loss of life. Fights between prison residents or fires that occur due to electrical shorts can eventually claim many lives because it is difficult to move due to a full prison. Currently in Indonesia there are 527 prisons. Meanwhile, the total capacity is 132,000 people. Currently in Indonesia, the prison population is almost 270,000. Therefore, the author tries to give an idea, what is the solution to reduce overcapacity in prisons, is it possible to establish a partnership with Islamic boarding schools? This is what I want to discuss in this article. Where in my research, using the library research method. Where is the conclusion that I got, it should be very possible for prisons, in this case the Regional Office of Law and Human Rights (KanwilkumHAM), to cooperate with Islamic boarding schools, because now the pattern of fostering inmates in the style of pesantren has begun.